Praseodymium-copper-aluminum co-doped SmCo5-based permanent magnet ribbon and preparation method thereof
Through the preparation method of SmCo5-based permanent magnet thin tape co-doped with praseodymium copper-aluminum, the problem of lack of rare earth element optimization and multi-combination regulation in the existing technology is solved, and the high magnetic performance of SmCo5-based permanent magnet thin tape is achieved. Coercive force of 16.2~35.7kOe and remanent magnetism of 41.4~58.4emu/g.
Patent Information
- Application Number
- CN202411670501.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-14
AI Technical Summary
The existing SmCo5-based permanent magnet strip ignores the optimization of rare earth elements when adding alloy elements, and the multivariate co-doping lacks regularity in the regulation of microstructure and magnetic properties, resulting in the magnetic properties not yet reaching a satisfactory level.
Using the co-doping method of praseodymium copper-aluminum, Pr, Cu and Al are added to the SmCo5-based alloy at the same time. The SmCo5-based permanent magnet strip with a multivariate complex phase microstructure was prepared by melt centrifugation and quick quenching technology to regulate Pr-Cu -Al added ratio to improve magnetic performance.
The coercive force and magnetization strength of the SmCo5-based permanent magnet thin strip are achieved while increasing the coercive force of the prepared thin strip is 16.2~35.7kOe, and the residual magnetism is 41.4~58.4emu/g. Form a typical cellular structure to increase coercivity.
Smart Images

Figure CN119314768A_ABST
Abstract
Description
Technical Field
[0001] The technical solution of the invention relates to the technical field of rare earth-cobalt-based permanent magnetic materials, and specifically is a method for preparing a SmCo5-based alloy thin strip magnet. Background Art
[0002] As an important basic material in the fields of modern power, electronics and information industry, rare earth permanent magnet materials play a vital role in daily life, industrial production, national defense and military. The rapid development of industrial technology has put forward higher requirements on the high temperature resistance and hard magnetic properties of permanent magnet materials. Therefore, SmCo5 permanent magnet alloy with excellent permanent magnetic properties and high temperature stability plays an irreplaceable role in high temperature application fields. However, the coercivity (H) of SmCo5 alloy at room temperature is c ) is far lower than 1 / 10 of the theoretical value, and the magnetization intensity is low, so obtaining high-performance SmCo5 permanent magnet materials is still one of the research hotspots in the field of rare earth permanent magnets.
[0003] Optimizing alloy composition is the most effective way to improve the magnetic properties of SmCo5-based alloys. Yan et al. (Yan AR, Zhang W Y, Zhang HW, et al. Magnetic properties of Sm-and Cu-doped oriented SmCo5 ribbons prepared by melt spinning [J]. Journal of Applied Physics, 2000, 88 (5): 2787-2790.) found that adding a small amount of Cu to SmCo5 ribbons can significantly improve the magnetic properties of the ribbons, and Sm (Co 0.8 Cu 0.2 )5 thin ribbon annealed at 650℃ has a coercivity of up to 12.4kOe. Tung et al. (Tung IC, Zhang HW, et al. Hard magnetic properties and microstructures of melt-spun SmCo5Fe x (x=0,1and 2)ribbons[J].Journal of Physics D:Applied Physics,1999,32(14):1587.) was prepared at a speed of 25m / s with a composition of Sm 1.2 The results show that the microstructure and phase composition of Co5Fe (x = 0, 1 and 2) ribbons depend on the Fe content. c =8.2kOe, M s =117.7emu / g,M r / Ms =0.62, which means that Fe doping can significantly improve the magnetization of SmCo5 thin ribbon. Saito et al. (Saito T, D Nishio-Hamane. Magnetic properties of SmCo 5-x Fe x (x=0-4)melt-spun ribbon[J].Journal ofAlloysandCompounds,2014,585:423-427.) found that the remanence of SmCo3Fe2 ribbon can reach 100emu / g, but the coercivity is only 2.9kOe. In general, Cu can improve the coercivity of SmCo5-based alloys, but Cu as a non-magnetic element will reduce the magnetization intensity of SmCo5 phase; the atomic magnetic moment of Fe is 2.2μB, which is significantly higher than the atomic magnetic moment of Co (1.7μB), so adding Fe element to SmCo5 alloy is the first choice to improve the magnetization intensity, but the exchange interaction of Fe-Co is weaker than that of Co-Co, which will reduce the anisotropy field.
[0004] In view of the low magnetization intensity of SmCo5 phase, researchers hope to use Fe with high magnetic moment to replace Co. However, Fe doping will reduce the coercivity of the alloy. Therefore, Suresh et al. (Suresh K, Gopalan R, Bhikshamaiah G, et al. Phaseformation, microstructure and magnetic properties investigation in Cu and Fesubstituted SmCo5 melt-spun ribbons[J]. Journal of Alloys and Compounds, 2008, 463(1): 73-77.) doped Cu and Fe at the same time and used different quenching rates to prepare Sm 17.24 Co 66.20 Cu 8.28 Fe 8.28 CN201710189603 discloses a method for preparing a Sm-Co based thin strip, which mainly adds different amounts of Alnico alloy into SmCo5 alloy, and prepares SmCo5 based thin strip magnet by melt quenching combined with heat treatment. At room temperature, its intrinsic coercivity is 19.2-34.9 kOe, and its remanence is 32.8-56.2 emu / g. CN201710189606 and CN201710189613 successively disclose the general formula of element composition Sm x Co y Al z Cuu Fe v 、Sm x Co y Cu z Fe u Cr v Si w Ti e Mo f SmCo5 type permanent magnetic thin strip. The above method mainly introduces SmCo5 in the form of multi-element doping, and the added elements are mostly simple Co substitution relationships. CN106298131A discloses a method for PrCo5 permanent magnet doped with PrCu alloy, that is, mixing amorphous PrCo5 alloy powder with PrCu amorphous powder and then preparing hot pressing-hot deformation magnets by spark plasma sintering. However, this method is to prepare high-performance permanent magnets by grain boundary doping, and does not involve the influence of element substitution on magnetic properties.
[0005] In general, one of the most effective methods for preparing Sm-Co compounds is to melt-quench the cast master alloy and then heat treat it. Adding trace elements and other elements in the preparation of SmCo5 thin strips has been one of the hot research in recent years, but adding a single element can only increase the coercivity or magnetization intensity alone, while composite doping can achieve simultaneous improvement of coercivity and remanence. So far, composite doping has mainly focused on the replacement of Co elements, and has not achieved regular regulation of microstructure by multi-element addition. There has been no report on the regular co-doping of SmCo5-based thin strip alloys using low-melting-point Pr-Cu-Al elements to simultaneously replace Sm and Co elements, and the magnetic properties of the thin strips still need to be further improved. Summary of the invention
[0006] The purpose of the present invention is to provide a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip and a preparation method thereof in view of the shortcomings of the current technology. The element composition formula of the SmCo5-based permanent magnetic thin strip is Sm x Pr y Co z Cu u Al v By adding Pr, Cu, and Al to the SmCo5 alloy at the same time and adjusting the addition ratio of Pr-Cu-Al, the regular multi-component composite addition to the SmCo5-based permanent magnetic ribbon is achieved. By this simultaneous addition method of replacing Sm and Co, a SmCo5-based permanent magnetic ribbon with a multi-component multi-phase microstructure system is prepared according to the idea of in-situ self-generation. This overcomes the defects of existing similar SmCo5-based permanent magnetic ribbons that ignore the optimization of rare earth elements when adding alloy elements, and the lack of regularity in the regulation of microstructure and magnetic properties by multi-component co-doping.
[0007] The technical solution adopted by the present invention to solve the technical problem is:
[0008] A praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip, whose elemental composition formula is Sm x Pr y Co z Cu u Al v , the subscripts x, y, z, u and v in the formula represent atomic percentages of the defined element composition ranges, 15.65≤Sm≤16.56, 78.27≤Co≤82.80, 0.44≤Pr≤4.17, 0.17≤Cu≤1.59, 0.03≤Al≤0.32, and in terms of atomic percentage, x+y+z+u+v=100;
[0009] The thickness of the thin strip is 20 to 75 μm, its intrinsic coercive force is 16.2 to 35.7 kOe at room temperature, and its remanence is 41.4 to 58.4 emu / g.
[0010] The method for preparing the SmCo5-based permanent magnetic thin strip adopts melt centrifugal quenching technology and comprises the following steps:
[0011] The first step is to prepare the raw materials:
[0012] According to the elemental composition formula Sm x Pr y Co z Cu u Al v The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 2wt% to 10wt% higher than the theoretically calculated mass, so as to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0013] The second step is to prepare SmCo5-based master alloy ingot:
[0014] Put all the raw materials prepared in the first step into the crucible of the vacuum arc melting furnace or vacuum induction melting furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2 Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0015] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0016] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10 - 2Pa, the master alloy ingot is melted again, and then the melt is rapidly quenched on a roller rotating at a peripheral speed of 10m / s to 60m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0017] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0018] The SmCo5-based quick-quenching thin strip prepared in the third step is annealed at 500°C to 700°C for 10min to 60min to obtain a Pr-Cu-Al co-doped SmCo5-based permanent magnetic thin strip, the elemental composition of which is Sm x Pr y Co z Cu u Al v The intrinsic coercivity of the permanent magnetic ribbon at room temperature is 16.2-35.7 kOe, and the remanence is 41.4-58.4 emu / g.
[0019] The raw materials used in the preparation method of the above-mentioned SmCo5-based permanent magnetic thin strip product are all commercially available, the equipment used are all well-known chemical equipment, and the process operation methods used are all well known to technicians in this technical field.
[0020] Compared with the prior art, the present invention has the following outstanding substantive features:
[0021] (1) In the current technology, CN201410189603 and CN201710189606 mainly add alloy elements to replace Co, increase the magnetization intensity of the thin strip by adding Fe, and obtain high coercivity by adding non-magnetic elements. In essence, the high coercivity is achieved by relying on the high anisotropy field of the SmCo5 phase. The above methods have obvious deficiencies in optimizing and regulating the regularity of the microstructure. The essential feature of the present invention is that Sm and Co are optimized and regulated simultaneously by co-doping, and Pr-Cu-Al alloy is added to SmCo5 to design (Sm, Pr) 1+x (Co,Cu,Al)5 alloy, constructs the SmCo5 / Sm2Co7 cellular microstructure system with the idea of in situ self-generation.
[0022] (2) In the composition design of the present invention, full consideration is given to the role of a single element in improving the magnetic properties of the SmCo5 phase itself, and the synergistic effect of multiple additions to the SmCo5-based alloy is comprehensively considered. Pr that can improve the magnetization intensity of the SmCo5 phase and Cu and Al that can improve the coercive force are selected to design a low-melting-point Pr-Cu-Al alloy. Based on this regular multiple addition, the synergistic effect of multiple magnetic mechanisms is introduced into the SmCo5-based thin ribbon magnet to achieve a simultaneous improvement in coercive force and magnetization intensity.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) Compared with the SmCo5-based thin ribbon magnet prepared by the prior art, the addition of Pr-Cu-Al alloy can form a typical complete cellular structure in the thin ribbon. Therefore, its coercivity comes from the pinning of the cellular Sm2Co7-type phase domain wall by the intracellular SmCo5-type phase domain wall, thereby significantly improving the coercivity of the SmCo5-based thin ribbon magnet.
[0025] (2) The present invention comprehensively considers the improvement of coercivity by cellular structure and the synergistic effect of multi-element addition of alloy elements to achieve simultaneous improvement of coercivity and magnetization, designs the composition of Pr-Cu-Al alloy, and realizes regular regulation and optimization of microstructure and magnetic properties through this regular multi-element addition;
[0026] (3) The SmCo5-based thin ribbon magnet prepared by the present invention has good magnetic properties. Its intrinsic coercive force is 16.2-35.7 kOe and its remanence is 41.4-58.4 emu / g at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0028] Figure 1 The Sm prepared in Example 1 16.14 Pr 2.15 Co 80.73 Cu 0.82 Al 0.16 X-ray diffraction pattern of permanent magnetic ribbon.
[0029] Figure 2 The Sm prepared in Example 1 16.14 Pr 2.15 Co 80.73 Cu 0.82 Al 0.16 Transmission electron micrograph of permanent magnetic ribbon.
[0030] Figure 3 The Sm prepared in Example 1 16.14 Pr 2.15 Co 80.73 Cu 0.82 Al 0.16 Hysteresis loop of permanent magnetic ribbon.
[0031] Figure 4 The Sm prepared in Example 2 16.56 Pr 0.44 Co 88.80 Cu 0.17 Al 0.03 X-ray diffraction pattern of permanent magnetic ribbon.
[0032] Figure 5 The Sm prepared in Example 2 16.56 Pr 0.44 Co 88.80 Cu 0.17 Al 0.03 Hysteresis loop of permanent magnetic ribbon.
[0033] Figure 6 The Sm prepared in Example 3 16.45 Pr 0.88 Co 82.27 Cu 0.33 Al 0.07 X-ray diffraction pattern of permanent magnetic ribbon.
[0034] Figure 7 The Sm prepared in Example 3 16.45 Pr 0.88 Co 82.27 Cu 0.33 Al 0.07 Hysteresis loop of permanent magnetic ribbon.
[0035] Figure 8 The Sm prepared in Example 4 15.84 Pr 3.37 Co 79.24 Cu 1.29 Al 0.26 X-ray diffraction pattern of permanent magnetic ribbon.
[0036] Fig. 9 The Sm prepared in Example 4 15.84 Pr 3.37 Co 79.24 Cu 1.29 Al 0.26 Hysteresis loop of permanent magnetic ribbon.
[0037] Fig.10 The Sm prepared in Example 5 15.65 Pr 4.17 Co 78.27 Cu 1.59 Al 0.32 X-ray diffraction pattern of permanent magnetic ribbon.
[0038] Fig.11 The Sm prepared in Example 5 15.65 Pr 4.17 Co 78.27 Cu 1.59 Al 0.32 Hysteresis loop of permanent magnetic ribbon.
[0039] Fig.12 The Sm prepared in Example 6 15.94 Pr 2.97 Co 79.73 Cu1.13 Al 0.23 X-ray diffraction pattern of permanent magnetic ribbon.
[0040] Fig.13 The Sm prepared in Example 6 15.94 Pr 2.97 Co 79.73 Cu 1.13 Al 0.23 Hysteresis loop of permanent magnetic ribbon. DETAILED DESCRIPTION
[0041] Example 1
[0042] The first step is to prepare the raw materials:
[0043] According to the elemental composition formula Sm 16.14 Pr 2.15 Co 80.73 Cu 0.82 Al 0.16 The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 6wt% higher than the theoretically calculated mass, so as to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0044] The second step is to prepare SmCo5-based master alloy ingot:
[0045] Put all the raw materials prepared in the first step into the crucible of the vacuum induction melting furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2 Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0046] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0047] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10 - 2 Pa, the master alloy ingot is melted again, and then the melt is rapidly quenched on a roller rotating at a peripheral speed of 40 m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0048] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0049] The SmCo5-based rapid-quenching thin strip prepared in the third step is annealed at 650°C for 20 minutes, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip product.
[0050] Figure 1The element composition of the sample prepared in this embodiment is Sm 16.14 Pr 2.15 Co 80.73 Cu 0.82 Al 0.16 X-ray diffraction pattern of the SmCo5-based permanent magnetic ribbon product. The ribbon is composed of SmCo5 phase and a small amount of Sm2Co7 phase.
[0051] Figure 2 The transmission electron microscope image of the SmCo5-based permanent magnetic thin strip product prepared in this embodiment is shown. It can be seen from the image that the thin strip presents a typical cellular structure, in which the cells are SmCo5-type phases and the cell walls are Sm2Co7-type phases.
[0052] Figure 3 The hysteresis loop of the SmCo5-based permanent magnetic thin strip product prepared in the embodiment is shown in the figure. 16.14 Pr 2.15 Co 80.73 Cu 0.82 Al 0.16 The intrinsic coercivity of the permanent magnetic ribbon at room temperature is 32.8kOe and the remanence is 58.4emu / g.
[0053] Example 2
[0054] The first step is to prepare the raw materials:
[0055] According to the elemental composition formula Sm 16.56 Pr 0.44 Co 88.80 Cu 0.17 Al 0.03 The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 5wt% higher than the theoretically calculated mass to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0056] The second step is to prepare SmCo5-based master alloy ingot:
[0057] Put all the raw materials prepared in the first step into the crucible of the vacuum arc melting furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2 Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0058] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0059] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10- 2 Pa, the master alloy ingot was melted again, and then the melt was rapidly quenched on a roller rotating at a peripheral speed of 10 m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0060] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0061] The SmCo5-based rapid-quenching thin strip prepared in the third step is annealed at 500°C for 10 minutes, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip product.
[0062] Figure 4 The element composition of the sample prepared in this embodiment is Sm 16.56 Pr 0.44 Co 88.80 Cu 0.17 Al 0.03 X-ray diffraction pattern of the SmCo5-based permanent magnetic ribbon product. The ribbon is composed of SmCo5 phase and a small amount of Sm2Co7 phase.
[0063] Figure 5 The demagnetization curve of the SmCo5-based permanent magnetic thin strip product prepared in this embodiment is shown in the figure. 16.56 Pr 0.44 Co 88.80 Cu 0.17 Al 0.03 The intrinsic coercivity of the permanent magnetic ribbon is 16.2kOe and the remanence is 44.5emu / g at room temperature.
[0064] Example 3
[0065] The first step is to prepare the raw materials:
[0066] According to the elemental composition formula Sm 16.45 Pr 0.88 Co 82.27 Cu 0.33 Al 0.07 The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 2wt% higher than the mass calculated theoretically, so as to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0067] The second step is to prepare SmCo5-based master alloy ingot:
[0068] Put all the raw materials prepared in the first step into the crucible of the vacuum arc melting furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0069] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0070] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10 - 2 Pa, the master alloy ingot was melted again, and then the melt was rapidly quenched on a roller rotating at a peripheral speed of 60 m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0071] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0072] The SmCo5-based rapid-quenching thin strip prepared in the third step is annealed at 600°C for 60 minutes, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip product.
[0073] Figure 6 The element composition of the sample prepared in this embodiment is Sm 16.45 Pr 0.88 Co 82.27 Cu 0.33 Al 0.07 X-ray diffraction pattern of the SmCo5-based permanent magnetic ribbon product. The ribbon is composed of SmCo5-type phase and a small amount of Sm2Co7-type phase.
[0074] Figure 7 The hysteresis loop of the SmCo5-based permanent magnetic thin strip product prepared in the embodiment is shown in the figure. 16.45 Pr 0.88 Co 82.27 Cu 0.33 Al 0.07 The intrinsic coercivity of the permanent magnetic ribbon at room temperature is 26.9kOe and the remanence is 47.1emu / g.
[0075] Example 4
[0076] The first step is to prepare the raw materials:
[0077] According to the elemental composition formula Sm 15.84 Pr 3.37 Co 79.24 Cu 1.29 Al 0.26The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 10wt% higher than the theoretically calculated mass, so as to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0078] The second step is to prepare SmCo5-based master alloy ingot:
[0079] Put all the raw materials prepared in the first step into the crucible of the vacuum arc melting furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2 Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0080] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0081] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10 - 2 Pa, the master alloy ingot was melted again, and then the melt was rapidly quenched on a roller rotating at a peripheral speed of 45 m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0082] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0083] The SmCo5-based rapid-quenching thin strip prepared in the third step is annealed at 600°C for 20 minutes, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip product.
[0084] Figure 8 The element composition of the sample prepared in this embodiment is Sm 15.84 Pr 3.37 Co 79.24 Cu 1.29 Al 0.26 X-ray diffraction pattern of the SmCo5-based permanent magnetic ribbon product. The ribbon is composed of SmCo5 phase and a small amount of Sm2Co7 phase.
[0085] Fig. 9 The hysteresis loop of the SmCo5-based permanent magnetic thin strip product prepared in the embodiment is shown in the figure. 15.84 Pr 3.37 Co 79.24 Cu 1.29 Al 0.26 The intrinsic coercivity of the permanent magnetic ribbon at room temperature is 35.7kOe and the remanence is 54.2emu / g.
[0086] Example 5
[0087] The first step is to prepare the raw materials:
[0088] According to the elemental composition formula Sm 15.65 Pr 4.17 Co 78.27 Cu 1.59 Al 0.32 The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 5wt% higher than the theoretically calculated mass to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0089] The second step is to prepare SmCo5-based master alloy ingot:
[0090] Put all the raw materials prepared in the first step into the crucible of the vacuum induction melting furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2 Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0091] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0092] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10 - 2 Pa, the master alloy ingot was melted again, and then the melt was rapidly quenched on a roller rotating at a peripheral speed of 55 m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0093] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0094] The SmCo5-based rapid-quenching thin strip prepared in the third step is annealed at 550°C for 30 minutes, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip product.
[0095] Fig.10 The element composition of the sample prepared in this embodiment is Sm 15.65 Pr 4.17 Co 78.27 Cu 1.59 Al 0.32 X-ray diffraction pattern of the SmCo5-based permanent magnetic ribbon product. The ribbon is composed of SmCo5 phase and a small amount of Sm2Co7 phase.
[0096] Fig.11 The hysteresis loop of the SmCo5-based permanent magnetic thin strip product prepared in the embodiment is shown in the figure.15.65 Pr 4.17 Co 78.27 Cu 1.59 Al 0.32 The intrinsic coercivity of the permanent magnetic ribbon at room temperature is 30.1 kOe and the remanence is 51.4 emu / g.
[0097] Example 6
[0098] The first step is to prepare the raw materials:
[0099] According to the elemental composition formula Sm 15.94 Pr 2.97 Co 79.73 Cu 1.13 Al 0.23 The required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 8wt% higher than the mass calculated according to the theory, so as to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials;
[0100] The second step is to prepare SmCo5-based master alloy ingot:
[0101] Put all the raw materials prepared in the first step into the crucible of the vacuum arc furnace, and evacuate the furnace body to make the vacuum degree in the furnace less than 5×10 -2 Pa, the furnace temperature rises to above the melting point of the raw material metal Co, so that the raw materials are completely melted and fully mixed to obtain a SmCo5-based master alloy ingot;
[0102] The third step is to prepare SmCo5-based alloy rapid quenching thin strip:
[0103] The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace and the vacuum in the furnace is evacuated to 5×10 - 2 Pa, the master alloy ingot was melted again, and then the melt was rapidly quenched on a roller rotating at a peripheral speed of 20 m / s to obtain a SmCo5-based alloy rapidly quenched thin strip;
[0104] Part 4: Preparation of SmCo5-based permanent magnetic ribbons:
[0105] The SmCo5-based rapid-quenching thin strip prepared in the third step is annealed at 700°C for 40 minutes, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip product.
[0106] Fig.10 The element composition of the sample prepared in this embodiment is Sm 15.94 Pr 2.97 Co 79.73 Cu 1.13 Al0.23 X-ray diffraction pattern of the SmCo5-based permanent magnetic ribbon product. The ribbon is composed of SmCo5 phase and a small amount of Sm2Co7 phase.
[0107] Fig.11 The hysteresis loop of the SmCo5-based permanent magnetic thin strip product prepared in the embodiment is shown in the figure. 15.94 Pr 2.97 Co 79.73 Cu 1.13 Al 0.23 The intrinsic coercivity of the permanent magnetic ribbon is 24.5kOe and the remanence is 41.1emu / g at room temperature.
[0108] In the above embodiments, the raw materials used are all commercially available, the equipment used are all well-known chemical equipment, and the process operation methods used are all well known to those skilled in the art.
Claims
1. A praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip, characterized by The elemental composition formula of the thin strip is SmxPryCozCuuAlv, where the subscripts x, y, z, u and v represent the atomic percentages that limit the elemental composition range, 15.65≤Sm≤16.56, 78.27≤Co≤82.80, 0.44≤Pr≤4.17, 0.17≤Cu≤1.59, 0.03≤Al≤0.32, and in terms of atomic percentage, x+y+z+u+v=100.
2. The praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin strip according to claim 1, characterized in that The ribbon has a thickness of 20 to 75 μm, an intrinsic coercive force of 16.2 to 35.7 kOe, and a remanence of 41.4 to 58.4 emu / g at room temperature.
3. The method for preparing the SmCo5-based permanent magnetic thin strip according to claim 1, characterized in that: The SmCo5-based permanent magnetic ribbon is co-doped with Sm and Co elements by using low melting point Pr-Cu-Al elements, and the addition ratio of Pr-Cu-Al is adjusted to achieve regular multi-component composite addition to the SmCo5-based permanent magnetic ribbon. The specific steps are as follows: The first step is to prepare the raw materials: The ingredients are prepared according to the atomic ratio of the elemental composition formula SmxPryCozCuuAlv, and the required mass of pure Sm, pure Co, pure Pr, pure Cu and pure Al are weighed for preparation. The actual mass of Sm weighed during the preparation is 2wt% to 10wt% higher than the theoretically calculated mass, so as to compensate for the volatilization of Sm during the smelting and rapid quenching process, thereby completing the preparation of the raw materials; The second step is to prepare SmCo5-based master alloy ingot: Put all the raw materials prepared in the first step into the crucible of a vacuum arc melting furnace or a vacuum induction melting furnace, evacuate the furnace body to make the vacuum degree in the furnace lower than 5×10-2Pa, raise the furnace temperature to above the melting point of the raw material metal Co, completely melt the raw materials and mix them fully, and obtain a SmCo5-based master alloy ingot; The third step is to prepare SmCo5-based alloy rapid quenching thin strip: The SmCo5-based master alloy ingot obtained in the second step is placed in a melt rapid quenching furnace, the vacuum in the furnace is evacuated to below 5×10-2Pa, the master alloy ingot is melted again, and then the melt is rapidly quenched on a roller rotating at a peripheral speed of 10m / s to 60m / s to obtain a SmCo5-based alloy rapid quenching thin strip; Part 4: Preparation of SmCo5-based permanent magnetic ribbons: The SmCo5-based quick-quenched thin ribbon prepared in the third step is annealed at 500℃~700℃ with a holding time of 10min~60min, thereby obtaining a praseodymium-copper-aluminum co-doped SmCo5-based permanent magnetic thin ribbon with an elemental composition formula of SmxPryCozCuuAlv. The permanent magnetic thin ribbon has an intrinsic coercive force of 16.2~35.7kOe and a remanence of 41.4~58.4emu / g at room temperature.
Citation Information
Patent Citations
Rotary table dynamic angular position error measurement precision improving device and rotary table dynamic angular position error measurement correcting method
CN105091835A
Method for preparing PrCo<5> permanent magnet doped with PrCu alloy through thermal deformation method
CN106298131A
SmCo5-based permanent magnet thin strip magnet and preparation method thereof
CN106710764A
SmCo5 permanent magnet ribbon magnet and preparation method thereof
CN106887291A
SMCO5-based permanent magnet strip magnet and preparation method thereof
CN106887292B